2010
DOI: 10.1128/jvi.01437-10
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Specific Determinants of Human APOBEC3F, APOBEC3C, and APOBEC3DE and African Green Monkey APOBEC3F That Interact with HIV-1 Vif

Abstract: Human APOBEC3F (hA3F) and human APOBEC3G (hA3G) are potent anti-human immunodeficiency virus (anti-HIV) host factors that suppress viral replication by hypermutating the viral genome, inhibiting reverse transcription, and hindering integration. To overcome hA3F and hA3G, HIV-1 encodes Vif, which binds and targets these host proteins for proteasomal degradation. Previously, we reported that the hA3F-Vif interactions that lead to hA3F degradation are located in the region comprising amino acids 283 to 300. We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
89
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(102 citation statements)
references
References 71 publications
12
89
0
1
Order By: Relevance
“…Previously, we and others found that the determinant in A3G for Vif1-induced degradation includes D128 and the surrounding residues (45, 55-57), and we found that the critical determinant in A3F for Vif1-induced degradation includes E289 and the surrounding residues (42,58). A3G D128K and GFG2 mutants (9) and A3F E289K and FGF4 mutants (7), were previously shown to be resistant to Vif1-induced degradation (Fig.…”
Section: Yrhhysupporting
confidence: 61%
See 3 more Smart Citations
“…Previously, we and others found that the determinant in A3G for Vif1-induced degradation includes D128 and the surrounding residues (45, 55-57), and we found that the critical determinant in A3F for Vif1-induced degradation includes E289 and the surrounding residues (42,58). A3G D128K and GFG2 mutants (9) and A3F E289K and FGF4 mutants (7), were previously shown to be resistant to Vif1-induced degradation (Fig.…”
Section: Yrhhysupporting
confidence: 61%
“…6, the A3FϾ5A mutant, in which A3F box 1 amino acids were replaced by alanines, was sensitive to Vif2. In addition, a chimera that we previously reported (42), in which residues 125 to 131 in box 1 of A3F were replaced by the corresponding residues of A3G, was Vif2 sensitive (Fig. 8B).…”
Section: Yrhhymentioning
confidence: 64%
See 2 more Smart Citations
“…A3F provides a unique opportunity to advance this goal because the crystal structure of its catalytic domain, which also binds Vif, has been solved (9,10). Previous studies have interrogated this interaction by manipulating human A3F (huA3F), which is normally sensitive to HIV-1 Vif-mediated degradation, to become resistant to Vif-mediated degradation (11)(12)(13). Here, the reciprocal approach is employed to determine the regions of A3F that mediate its sensitivity to HIV-1 Vif.…”
mentioning
confidence: 99%